Evaluating the Effectiveness of Benson Relaxation on Dysmenorrhea Pain Intensity: A Pre-Experimental Study Among Indonesian Female University Students - Febriana Febriana; Indah Lestari (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Dysmenorrhea is a prevalent menstrual disorder among young women that can impair daily functioning and quality of life. Although pharmacological treatments are commonly used, they may cause side effects, leading to increased interest in non-pharmacological approaches such as Benson relaxation. Objective: This study aimed to evaluate the effectiveness of Benson relaxation in reducing dysmenorrhea pain intensity among female university students. Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted involving 35 female students selected through purposive sampling. Participants received a 15-minute Benson relaxation session in a quiet and comfortable environment. Pain intensity was measured before and after the intervention using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon Signed-Rank Test. Results: The findings showed a statistically significant reduction in dysmenorrhea pain intensity following the intervention (Z = -5.257; p < 0.001). The median pain score decreased from 6 to 3. Before the intervention, most participants experienced moderate and severe pain, whereas after the intervention, pain levels shifted to mild and moderate categories. Conclusion: Benson relaxation is an effective, simple, and low-cost non-pharmacological intervention for reducing dysmenorrhea pain intensity. It can be applied in nursing practice and self-care, although further research using controlled designs is recommended